2008
DOI: 10.1007/s00253-007-1328-7
|View full text |Cite
|
Sign up to set email alerts
|

Dekkera and Brettanomyces growth and utilisation of hydroxycinnamic acids in synthetic media

Abstract: Dekkera and Brettanomyces yeast are important spoilage organisms in a number of food and beverage products. Isolates of both genera were cultured in a defined medium and supplemented with hydroxycinnamic acids and vinylphenols to investigate their influence on growth and the formation of ethyl phenol derivatives. The growth rate of Brettanomyces species in the presence of acids was reduced, and no significant conversion to vinyl or ethyl derivatives was observed. The growth rate and substrate utilisation rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 53 publications
5
31
1
Order By: Relevance
“…At 100 mg/L pcoumaric acid extended the duration of the lag phase from 2 (control) to 15 h (Table 2), while ferulic acid and caffeic acid increased lag phase to 16.5 and 12 h, respectively. Similar results showing a longer lag phase have been reported for S. cerevisiae growing in media supplemented with p-coumaric acid (Baranowski et al, 1980) and for D. bruxellensis exposed to p-coumaric acid (Dias et al, 2003) and ferulic acid (Harris et al, 2008(Harris et al, , 2010.…”
Section: Inhibition Of Yeast Growth By Hydroxycinnamic Acidssupporting
confidence: 78%
See 2 more Smart Citations
“…At 100 mg/L pcoumaric acid extended the duration of the lag phase from 2 (control) to 15 h (Table 2), while ferulic acid and caffeic acid increased lag phase to 16.5 and 12 h, respectively. Similar results showing a longer lag phase have been reported for S. cerevisiae growing in media supplemented with p-coumaric acid (Baranowski et al, 1980) and for D. bruxellensis exposed to p-coumaric acid (Dias et al, 2003) and ferulic acid (Harris et al, 2008(Harris et al, , 2010.…”
Section: Inhibition Of Yeast Growth By Hydroxycinnamic Acidssupporting
confidence: 78%
“…This inhibition of cell growth can be expected since HCAs act as antimicrobial agents (Baranowski et al, 1980). Similar results have been reported previously showing that ferulic acid at 388 mg/L inhibited the growth of several D. bruxellensis strains (Harris et al, 2008). Positive effects of HCAs on the growth rate of different isolates of Dekkera/Brettanomyces spp.…”
Section: Inhibition Of Yeast Growth By Hydroxycinnamic Acidssupporting
confidence: 76%
See 1 more Smart Citation
“…and its ascosporogenous form Dekkera are well recognized for contributing to the volatile phenylpropanoid content of wines by breaking down hydroxycinammic acids to vinyl phenols and subsequently to ethyl phenols; the ethyl phenols are considered detrimental to consumer acceptability of wine, contributing leather and barnyard characters to the wine (Chatonnet et al 1992, Lattey et al 2010, Wedral et al 2010. Brettanomyces and Dekkera yeast have a phenolic acid decarboxylase enzyme that converts hydroxycinnamic acids to their vinyl derivatives, which are the substrates of a second enzyme, vinylphenol reductase, whose activity results in the formation of ethylphenols (Harris et al 2008). Many bacteria, fungi, and yeast have vinylphenol reductase activity, but under enological conditions it is predominantly Brettanomyces and Dekkera yeast that produce ethylphenols (Chatonnet et al 1993, Suárez et al 2007).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…Also, studies have been carried out to understand the mechanisms of 4-vinylphenol and 4-ethylphenol production (Dias et al, 2003;Godoy et al, 2008;Harris et al, 2008;Harris et al, 2009). Barata et al (2008) concluded that the production of 4-ethylphenol in red wines is related to the presence of growing populations of D. bruxellensis, demonstrating that the primary management objective should not be their complete elimination but their maintenance at constant levels.…”
Section: The Production Of Volatile Phenols By Brettanomyces/dekkeramentioning
confidence: 99%